A gestão do desenvolvimento de competências e a empregabilidade do gerente de projetos: um estudo de caso de tecnologia da informação de uma instituição bancária - Pereira, Sirlei de Almeida (2014)
The purpose of this research was to investigate how the skills development management influences the competences and the employability of project managers. A justification focuses on the theme relevance for business strategies of this segment where there is a strong demand for technological projects. Furthermore the continuous development of project manager skills is being required for financial institutions. Accordingly this survey sought to understand how skills development influences the skills and employability, specifically addressing the profile of this professional. To achieve the established goals was done a qualitative study based on the case of a Brazilian headquarters of the information technology area at an international bank organization. Data were collected using a quantitative information survey, documentary research and semi-structured interviews with project managers and were analyzed using by comparison standard of the reference literature. As a result it was found that although there is an institutional development program there are difficulties on having a useful access to it. Nevertheless, it was found a positive impact in employability and on the project manager skills, leveraged through experience and coaching. It was also concluded that the project managers have acknowledged possess a high level of employability promoted mainly by the lack of trained professionals in this sector. Finally , this research found that the employability of a project manager is the result of experience in projects , adequacy of skills available and the skills required, besides coming from a good a contacts relationship who knows the history of this professional in conducting projects successfully.